Identifying Contractorsâ Planned Quality Costs in Indonesian Construction Projects - Marzuki, Puti F.; Wisridani, M. (ITB Journal Publisher, LPPM ITB, 2014)
InÂ a very competitive construction industry, quality costs have to be measuredÂ toÂ beÂ ableÂ toÂ identifyÂ potentialÂ qualityÂ problemÂ areasÂ andÂ toÂ focus attentionÂ onÂ workÂ outputÂ improvementÂ opportunities.Â TheÂ awarenessÂ of contractors on the importance of quality costs could be reflected in the extent of theirÂ qualityÂ costsÂ planning.Â ThisÂ paperÂ presentsÂ anÂ identificationÂ ofÂ planned qualityÂ costsÂ inÂ threeÂ constructionÂ projectsÂ executedÂ byÂ twoÂ largeÂ Indonesian contractors,Â aÂ state-ownedÂ companyÂ andÂ aÂ privateÂ companyÂ inÂ Jakarta.Â The objective is to enable the contractors to elaborate their quality costs planning and thereby improve their work output based on the findi ngs. QualityÂ costsÂ areÂ first grouped intoÂ threeÂ categories: prevention, appraisal,Â andÂ failureÂ costs.Â Based on theÂ worksÂ ofÂ previousÂ researchers,Â aÂ listÂ ofÂ qualityÂ managementÂ activitiesÂ that should be covered in each quality costs category is then created. The contractorsâ planned quality costs dataÂ for each category areÂ identified andÂ collected through interviewsÂ andÂ questionnaireÂ surveysÂ thatÂ Â referÂ toÂ theÂ list.Â QualityÂ costsÂ are expressedÂ asÂ aÂ percentageÂ ofÂ contractÂ value.Â ItÂ isÂ revealedÂ thatÂ althoughÂ large contractorsÂ alreadyÂ haveÂ certainÂ knowledgeÂ onÂ qualityÂ costsÂ inÂ construction projects,Â these costs areÂ not planned in a structured wayÂ through an analysis of systematicÂ qualityÂ costsÂ records.Â ThroughÂ costÂ categorizationÂ itÂ isÂ alsoÂ shown that higher prevention and appraisal costs lead to lower failure costs.Â It is then concludedÂ thatÂ aÂ lotÂ ofÂ workÂ isÂ stillÂ toÂ beÂ doneÂ byÂ theÂ contractorsÂ toÂ setÂ upÂ a qualityÂ costsÂ recordingÂ systemÂ whichÂ canÂ serveÂ asÂ aÂ basisÂ forÂ theirÂ quality improvement planning.